2015
DOI: 10.1007/s13277-015-4223-3
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of MALAT-1 and its association with survival rate and the effect on cell cycle and migration in patients with esophageal squamous cell carcinoma

Abstract: The aim of this study is to investigate whether metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1) can be used as a potential therapy target for human esophageal squamous cell carcinoma. MALAT-1 expression levels were detected in 137 paired EC samples and adjacent nonneoplastic tissues. Human esophageal carcinoma cell lines EC9706 and KYSE150 were transfected with MALAT-1 small interference RNA. Cell proliferation, migration/invasion ability, cell cycle, and apoptosis were assessed. MALAT-1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…MALAT1 potentiated the epithelial-mesenchymal transition and angiogenesis by regulating miR-126-5p activity in colorectal cancer [10]. Additionally, MALAT1 promotes the migration and proliferation in ESCC [13,14]. These results suggest that MALAT1 may have opposite effects in different tumors.…”
mentioning
confidence: 85%
“…MALAT1 potentiated the epithelial-mesenchymal transition and angiogenesis by regulating miR-126-5p activity in colorectal cancer [10]. Additionally, MALAT1 promotes the migration and proliferation in ESCC [13,14]. These results suggest that MALAT1 may have opposite effects in different tumors.…”
mentioning
confidence: 85%
“…There have been several reports of involvement of lncRNAs in esophageal cancer, but most of these investigations focused on ESCC and therefore fall outside the scope of this review 38,39,40,41,42,43,44 . One recent comprehensive study of lncRNA expression evaluated 5037 human tumor specimens, of 13 distinct cancer types 45 .…”
Section: Lncrnas In Be and Eacmentioning
confidence: 99%
“…Previous studies have shown that lncRNAs play crucial roles in the occurrence and development of ESCC (Wu et al , ; Yao et al , ; Zhang et al , ). In our study, the most notable finding was that the noncoding function of NELFA mRNA plays an important role in oesophageal cancer progression.…”
Section: Discussionmentioning
confidence: 99%